Aplicação do incidente de desconsideração da personalidade jurídica previsto no Código de Processo Civil aos pedidos de redirecionamento de execuções fiscais - Quedevez, Erick Marques (2017)
This study aims to evaluate the possibility application of procedure baptized of "incident of disregard of legal entity", foreseen by the articles 133-137 of the Code of Civil Procedure, to the issue involving the requests for redirection of tax executions based on article 135 of the National Tax Code and in the precedent number 435 of the superior court of justice. To investigate the applicability of this procedure to redirection requests, we present the main material and formal limits that must be followed by the judges that create such decisions. To reach this goal, we present, initially, the theoretical premises that support this research and we investigate the inflows of the rules of structures on the procedure of legal enunciation, especially to demonstrate the consequences that a defective enunciation can bring to redirection decision. Finally, we present the reasons that justify the necessary applicability of the incident of disregard of the legal personality to the requests for redirection of tax executions and indicate the limitations of this procedure when applied to relationships of a tax nature.